Food Allergy Education and Management in Early Learning and Childcare Centres: A Scoping Review on Current Practices and Gaps - Mae Jhelene L. Santos; Kaitlyn A. Merrill; Moshe Ben-Shoshan; Jennifer D. Gerdts; Don Giesbrecht; Elana Lavine; Susan Prentice; Julia Upton; Jennifer L. P. Protudjer (MDPI AG, 2023)
Anaphylaxis has occurred in preschools/schools yet there are no consistent food allergy (FA) management practices in early learning and childcare centres (ELCC) across jurisdictions. Presently, there are no reviews that have synthesized FA-related knowledge and management practices within ELCC. We aimed to perform a scoping review of FA management in ELCC, and report on perceived gaps or barriers. A PRISMA-ScR-guided search was conducted for North American, European and Australian articles in English/French in the OVID-MedLine, Scopus, and PsycInfo databases. Two independent reviewers screened the titles/abstracts of 2010 articles and full-text screened 77 articles; 15 of which were specifically related to ELCC. If the two reviewers could not agree to the relevance of a given study, a third reviewer provided guidance. This third reviewer also screened French articles. Thematic and descriptive reports of the studies were presented. We reported solely on pre-Coronavirus Disease pandemic ELCC studies. We included ten articles in this review, which provide evidence that ELCC staff have variable baseline knowledge, comprehension, experience, and practices in place to manage FA. ELCC staff also have limited FA-related training and experience regarding administration of epinephrine auto-injectors (EAI). Emergency Anaphylaxis Plans (EAP) were described in four studies. One study reported the parental influence on the site's food purchasing and FA management. Three studies provided educational interventions, which demonstrated increased and sustained FA-related knowledge and confidence post-intervention. Participants deemed the training beneficial and desired annual training and more FA resources to be available. Across jurisdictions, ELCC staff have provided care and administered EAI in emergencies, but training remained variable. Communication and care planning amongst ELCC staff, and parents, is crucial. Annual education, available EAI and EAPs are tools necessary for effectively managing emergencies.